PRELIMINARY INVESTIGATION OF THE PROTEIN PORTION OF SOME OF THE MUCOPROTEINS OF THE EYE - MASSIEU H , GUILLERMO; CRAVIOTO, RENE O (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
By use of a sifting technique in sand pits of Zumpango de Ocampo, numerous subfossil remains, of late Pleistocene or Recent age, were discovered None of the remains were gener-ically identified, but they were referred temporarily to the amphibian familie
CIENC MEX
Keywords: INVESTIGATION, PROTEIN, MUCOPROTEINZ, EYE; MULTIDISCIPLINARIA; CIENCIAS CLINICAS; OFTAMOLOGIA